Mobilitas Permanen: Backpacking sebagai Karier Subkultural Kaum Muda Nomad Kontemporer - Sidiq Hari Madya (Universitas Gadjah Mada, 2020)
Backpacking seems to become a cultural symbol of contemporary youth nomadism. Backpackers arrange their own trip with more flexible itinerary and construction of identity that often opposes tourists’ identity. The characteristics of their travel makes backpacker capable of forming their own travel subculture. By interviewing 15 Indonesian backpackers and intensively observing their travel journeys posted online in backpacker forum and their social media pages, this study explores the backpacking activity as a potential for subcultural career among today’s traveling youth. Three types of backpacker subcultural career are identified under the headline of open trip, endorsed trip and business trip. This finding contributes to enrich backpacker discussion in the frame of traveling as a work activity.